Newborn Screening for Critical Congenital Heart Disease in a Low-Resource Setting; Research Protocol and Preliminary Results of the Tanzania Pulse Oximetry Study - Naizihijwa Majani; Pilly Chillo; Martijn G. Slieker; Godwin Sharau; Vivienne Mlawi; Stella Mongella; Deogratias Nkya; Sulende Khuboja; Gideon Kwesigabo; Appolinary Kamuhabwa; Mohamed Janabi; Diederik Grobbee (Ubiquity Press, 2022)
Background: Critical Congenital Heart Disease (CCHD) is the leading cause of early new-born mortality. Its early detection and intervention is crucial for the survival of affected new-born. Pulse Oximetry (POX) has shown to be one of the feasible, accurate and cost-effective tools in screening CCHD in developed nations, it is yet to be practiced and established as standard of care in a low-resource setting. Objectives: This paper reports on the research protocol and preliminary results of an ongoing study regarding the performance of POX in detecting CCHD in new-borns in a low resource setting. Secondary objectives include investigating the burdens of CCHD and outcome at 12 months of age. Methods: The Tanzanian Pulse Oximetry Study (TPOXS) is a prospective cohort study which plans to enrol 30,000 mothers and new-borns delivered at two referral hospitals in Tanzania. New-borns are offered POX test 12 hours after birth, those positively undergoes echocardiography examinations. Confirmed with CCHD are placed under observation for up to first birthday. Results: During a 5-months pilot period, a total of 1,592 infants at the Muhimbili National Hospital, received POX test .65% of them were post-caesarean section and 52% being male. Most babies delivered through Spontaneous Vertex Delivery (SVD) were promptly discharge and did not get screened. The detection-rate of CCHD was 2.5 per 1,000 live births (at 95% confidence interval [CI] 0.9 to 6.7 per 1000 live birth); with a POX false positive rate of 0.6%. Seven false-positive infants out of 10 were found to carry significant other neonatal conditions, including persistent pulmonary hypertension of the new-born, transient tachypnoeic and neonatal sepsis. Conclusion: This paper provides the protocol of the ongoing TPOXS with the preliminary results showing prevalence matching closely the global data. It shows acceptability of POX screening for CCHD in a well-prepared low resource setting. Highlight: This study addresses the utilization of pulse oximeter in detecting critical congenital heart disease (CCHD) in a low-resource setting (such as sub-Saharan African countries).